2012
DOI: 10.1183/09031936.00091411
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to second-hand smoke and reproductive outcomes depending on maternal asthma

Abstract: Tobacco consumption and exposure to second-hand smoke (SHS) are associated with reduced birth weight. One issue that has not been clarified previously is that of the potential higher risk of this outcome in mothers with asthma. We assessed the role of prenatal maternal tobacco use and SHS on reproductive outcomes and assessed the interaction with maternal history of asthma.Data was collected from the INMA study, a maternal birth cohort selected from the general population established in Spain in 2002. We measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Meta-analyses of studies among non-smoking women have shown that SHS exposure during pregnancy was associated with a 1.32 (95% CI 1.07 to 1.63; p = 0.02) times increased risk of low birth weight and a 1.23 (95% CI 1.09 to 1.38; p < 0.001) times increased risk of stillbirth 3 4 . Furthermore, a dose-dependent inverse relationship between maternal urinary cotinine levels (as a proxy for SHS exposure) and offspring birth weight has recently been described 29 . Contemporary studies assessing the impact of SHS exposure on neonatal mortality are however lacking 4 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analyses of studies among non-smoking women have shown that SHS exposure during pregnancy was associated with a 1.32 (95% CI 1.07 to 1.63; p = 0.02) times increased risk of low birth weight and a 1.23 (95% CI 1.09 to 1.38; p < 0.001) times increased risk of stillbirth 3 4 . Furthermore, a dose-dependent inverse relationship between maternal urinary cotinine levels (as a proxy for SHS exposure) and offspring birth weight has recently been described 29 . Contemporary studies assessing the impact of SHS exposure on neonatal mortality are however lacking 4 30 .…”
Section: Discussionmentioning
confidence: 99%
“…This susceptibility occurs from conception since the intra‐uterine microenvironment is pivotal in sustaining fetal development as well as re‐shaping of the epigenome. Certain exposures during pregnancy such as adverse nutrition, smoking and maternal diseases are known to effect both fetal outcomes such as still births, fetal growth restriction and predisposition to variety of diseases . Asthma is one of the most common medical illnesses to complicate pregnancy, with prevalence of 12% in Australia .…”
Section: Introductionmentioning
confidence: 99%
“…Adjusted by height at four years, maternal weight gain during pregnancy, pre-pregnancy BMI, mother passive smoke exposure during pregnancy. 2 Adjusted by height at 4 years, maternal weight gain during pregnancy, pre-pregnancy BMI, gestational age (week), maternal age, social class, parity, mother passive smoke exposure during pregnancy. 3 Adjusted by height at 4 years, maternal weight gain during pregnancy, pre-pregnancy BMI, gestational age (week), maternal age, maternal education, social class, parity, mother passive smoke exposure during pregnancy.…”
Section: Resultsmentioning
confidence: 99%
“…Tobacco use and passive smoking during pregnancy can exert multiple effects on offspring, which may persist into adulthood [ 1 , 2 ]. Passive exposure to cigarette smoke in childhood is a global public health problem associated with respiratory symptoms, increased risk of invasive meningococcal disease, and high blood pressure [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%